2007
DOI: 10.1016/j.media.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Fisher discriminant for shape-based classification in epilepsy

Abstract: In this paper, we present the application of Kernel Fisher Discriminant in the statistical analysis of shape deformations that indicate the hemispheric location of an epileptic focus. The scans of two classes of patients with epilepsy, those with a right and those with a left medial temporal lobe focus (RATL and LATL), as validated by clinical consensus and subsequent surgery, were compared to a set of age and sex matched healthy volunteers using both volume and shape based features. Shapebased features are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…9. Studies have shown that distinguishing between LATL and RATL in epilepsy is a hard problem and that we need sophisticated features in order to automatically classify them (Kodipaka et al (2007)). Tables 2 and 3 indicate that the indices for both LATL and RATL are similar hence the left and right anterior medial temporal lobe focuses are indistinguishable w.r.t.…”
Section: Shape Variation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…9. Studies have shown that distinguishing between LATL and RATL in epilepsy is a hard problem and that we need sophisticated features in order to automatically classify them (Kodipaka et al (2007)). Tables 2 and 3 indicate that the indices for both LATL and RATL are similar hence the left and right anterior medial temporal lobe focuses are indistinguishable w.r.t.…”
Section: Shape Variation Analysismentioning
confidence: 99%
“…volume based analysis. A promising immediate avenue for future research (following Kodipaka et al (2007)) is to utilize the histogram of the deformation field between the shape complex of the subject and the atlas for further analysis. In our approach, a single distance transform is used to represent a shape complex.…”
Section: Shape Variation Analysismentioning
confidence: 99%
“…the intersection of two hyperplanes. With these constraints, the boundary (Eqn.2) in ℋ can also be written as: (7) Since ℋ ≡ ℝ M − 2 , let us track the section of the discriminant boundary, ∩ ℋ. Let X ∈ ℋ and the distance between a focus point F k and its orthogonal projection in ℋ, be .…”
Section: Finding Nearest Point For Fixed {H 1 (X) H 2 (X)}mentioning
confidence: 99%
“…We encounter such high dimensional sparse datasets in several computer vision and learning applications, such as in the diagnosis of Epilepsy based on brain MRI scans [7], the diagnosis of various types of Cancer from micro-array gene expression data [1], and speech recognition. Stated formally, the supervised learning problem is severely under constrained when one is given N labeled data points that lie in ℝ M where N ≪ M.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent approach proposes an entropy based criterion to find shape correspondences, but requires implicit surface representations [9]. Other recent methods combine the shape analysis with the search for correspondences, however, these methods are not easily adaptable to multiple observations of unstructured point sets [10,11,12] or focus only on the mean shape [13]. In order to build an SSM based on inexact correspondences between point clouds, we pursue a probabilistic concept and base our work on a EM-ICP registration algorithm which proved to be robust, precise, and fast [14].…”
Section: Introductionmentioning
confidence: 99%